Predominant Role of Plasmacytoid Dendritic Cells in Stimulating Systemic Autoimmunity - Huang, Xinfang; Dorta-Estremera, Stephanie; Yao, Yihong; Shen, Nan; Cao, Wei (Frontiers in Immunology, 2015)
Plasmacytoid dendritic cells (pDCs), which are prominent type I interferon (IFN-I)-producing immune cells, have been extensively implicated in systemic lupus erythematosus (SLE). However, whether they participate critically in lupus pathogenesis remains unknown. Recent studies using various genetic and cell type–specific ablation strategies have demonstrated that pDCs play a pivotal role in the development of autoantibodies and the progression of lupus under diverse experimental conditions. The findings of several investigations highlight a notion that pDCs operate critically at the early stage of lupus development. In particular, pDCs have a profound effect on B-cell activation and humoral autoimmunity in vivo. This deeper understanding of the vital role of pDCs in lupus pathogenesis supports the therapeutic targeting of the pDC-IFN-I pathway in SLE.